The guanine nucleotide exchange factor Vav3 intervenes in the migration pathway of oligodendrocyte precursor cells on tenascin-C - Schäfer, Ina; Bauch, Juliane; Wegrzyn, David; Roll, Lars; van Leeuwen, Simon; Jarocki, Annika; Faissner, Andreas (Frontiers in Cell and Developmental Biology, 2022)
Oligodendrocyte precursor cells (OPCs) are the exclusive source of myelination in the central nervous system (CNS). Prior to myelination, OPCs migrate to target areas and mature into myelinating oligodendrocytes. This process is underpinned by drastic changes of the cytoskeleton and partially driven by pathways involving small GTPases of the Rho subfamily. In general, the myelination process requires migration, proliferation and differentiation of OPCs. Presently, these processes are only partially understood. In this study, we analyzed the impact of the guanine nucleotide exchange factor (GEF) Vav3 on the migration behavior of OPCs. Vav3 is known to regulate RhoA, Rac1 and RhoG activity and is therefore a promising candidate with regard to a regulatory role concerning the rearrangement of the cytoskeleton. Our study focused on the Vav3 knockout mouse and revealed an enhanced migration capacity of Vav3−/− OPCs on the extracellular matrix (ECM) glycoprotein tenascin-C (TnC). The migration behavior of individual OPCs on further ECM molecules such as laminin-1 (Ln1), laminin-2 (Ln2) and tenascin-R (TnR) was not affected by the elimination of Vav3. The migration process was further investigated with regard to intracellular signal transmission by pharmacological blockade of downstream pathways of specific Rho GTPases. Our data suggest that activation of RhoA GTPase signaling compromises migration, as inhibition of RhoA-signaling promoted migration behavior. This study provides novel insights into the control of OPC migration, which could be useful for further understanding of the complex differentiation and myelination process.